Perspectives of people with schizophrenia on clinical outcome scales and patient-reported outcome measures: a qualitative study - Utako Sawada; Asami Matsunaga; Ayano Taneda; Natsu Sasaki; Sosei Yamaguchi (BMC Psychiatry)
Abstract Background Over the past half-century, numerous scales have been designed to quantify outcomes in people with severe mental health disorders. However, little is known about the views of people diagnosed with schizophrenia on individual outcome scales, particularly outside of European countries. Aim We conducted a qualitative study to examine the perspectives of people with schizophrenia on multiple scales in Japan. Methods Eleven participants took part in focus group interviews. Five had extensive experience as mental health peer supporters; the others had no such experience. To address potential power imbalances and facilitate dynamic discourse, participants were intentionally divided into two groups on the basis of peer support experience, and two simultaneous two-hour focus group interviews were conducted in separate rooms. The participants reviewed 12 clinical and patient-reported outcome measures and discussed their views on each measure. Interview data for each group were combined prior to analysis and qualitatively analyzed by four researchers using a thematic analysis approach. Results The average age of the participants was 42.7 years (SD = 8.3), and six were male. On average, the participants had been living with schizophrenia for 22.2 years (SD = 11.1). After analyzing the interview data, the following five themes were identified, each containing two to seven subthemes: 1) validity and format of the scale construct, 2) factors affecting the accuracy of responses, 3) plain language and familiar words in Japanese culture, 4) psychological impact on the respondents, and 5) containing important items in everyday life. Conclusion The participants provided both favorable and unfavorable feedback on each scale. When implementing research utilizing clinical outcome scales and patient-reported outcome measures, researchers should exercise caution considering the potential emotional impact on respondents. Furthermore, scale development should take into account the cultural background and psychological burden experienced by the respondents.